2017
DOI: 10.1007/s00432-017-2453-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival of melanoma patients treated with novel drugs: retrospective analysis of real-world data

Abstract: Novel drugs for melanoma provide a significant advantage in survival over classic chemotherapy. Comparative assessment of IPI and VEM indicated no difference, but only immunotherapy-treated patients achieved long-lasting results. Our data on sequential treatment indicate that immunotherapy might be a better option for the first line rather than targeted therapy, but that conclusion requires further studies of the best way to manage the treatment of melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…To date, only one published study has examined the real-world comparative effectiveness of second-line ipilimumab compared to standard chemotherapy. This study, conducted in Poland, found similar survival benefit as the trial (adjusted HR = 0.65), but observed differences in median OS from the clinical trial experience, including attenuated median OS and less evident survival tail plateau compared to that observed in the trial [2,5]. Additionally, correction for possible lead-time bias or differences in patient comorbidity between groups was not undertaken and notably the comparison group was contemporary rather than historic.…”
Section: Introductionmentioning
confidence: 74%
“…To date, only one published study has examined the real-world comparative effectiveness of second-line ipilimumab compared to standard chemotherapy. This study, conducted in Poland, found similar survival benefit as the trial (adjusted HR = 0.65), but observed differences in median OS from the clinical trial experience, including attenuated median OS and less evident survival tail plateau compared to that observed in the trial [2,5]. Additionally, correction for possible lead-time bias or differences in patient comorbidity between groups was not undertaken and notably the comparison group was contemporary rather than historic.…”
Section: Introductionmentioning
confidence: 74%
“…1 In recent years, novel drugs for melanoma have provided a significant advantage in survival over classic chemotherapy, especially for immunotherapy-treated patients, achieving long-lasting results in terms of overall survival. 2 Ipilimumab was the first immunotherapeutic drug that demonstrated a survival benefit over the long-standing standard therapy with dacarbazine in advanced melanoma. 3 Costs associated with cutaneous melanoma have been extensively discussed and reviewed in literature, 4,5 but new scenarios are opening up because the new immunotherapeutic drugs are very expensive treatments and are likely to cause an increasing economic impact on public and private healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, novel drugs for melanoma have provided a significant advantage in survival over classic chemotherapy, especially for immunotherapy-treated patients, achieving long-lasting results in terms of overall survival. 2 Ipilimumab was the first immunotherapeutic drug that demonstrated a survival benefit over the long-standing standard therapy with dacarbazine in advanced melanoma. 3…”
Section: Introductionmentioning
confidence: 99%
“…To date, only low-quality evidence is available to inform treatment sequencing decisions, but randomized studies are currently underway. Retrospective analyses, mostly involving ipilimumab, have suggested that prior treatment with a BRAFi is associated with an inferior response to subsequent immunotherapy [ 19 21 ], whereas recent analyses involving nivolumab and pembrolizumab are more controversial [ 22 , 23 , 25 27 ]. In the current analysis, patients who received initial ppRx with immunotherapy or targeted therapy had similar OS outcomes across the cobimetinib plus vemurafenib, vemurafenib monotherapy, and dacarbazine cohorts.…”
Section: Discussionmentioning
confidence: 99%